2009
DOI: 10.1364/oe.17.022474
|View full text |Cite
|
Sign up to set email alerts
|

Cryogenic spectroscopy of ultra-low density colloidal lead chalcogenide quantum dots on chip-scale optical cavities towards single quantum dot near-infrared cavity QED

Abstract: We present evidence of cavity quantum electrodynamics from a sparse density of strongly quantum-confined Pb-chalcogenide nanocrystals (between 1 and 10) approaching single-dot levels on moderately high-Q mesoscopic silicon optical cavities. Operating at important near-infrared (1500-nm) wavelengths, large enhancements are observed from devices and strong modifications of the QD emission are achieved. Saturation spectroscopy of coupled QDs is observed at 77K, highlighting the modified nanocrystal dynamics for q… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 58 publications
(74 reference statements)
0
9
0
Order By: Relevance
“…On bare glass, single nanocrystals were more easily discernible with ~ 170 counts per millisecond, while on graphene, the photon counts from the single nanocrystals are lower, ~ 100 counts per millisecond. Photon collection at the individual or few nanocrystal level allows us to gain insight into the exciton radiative and non-radiative relaxation rates [22][23] which can be masked by ensemble inhomogeneous broadening. As shown by the circled points of interest in Figure 2, individual nanocrystals were selected for lifetime measurements.…”
mentioning
confidence: 99%
“…On bare glass, single nanocrystals were more easily discernible with ~ 170 counts per millisecond, while on graphene, the photon counts from the single nanocrystals are lower, ~ 100 counts per millisecond. Photon collection at the individual or few nanocrystal level allows us to gain insight into the exciton radiative and non-radiative relaxation rates [22][23] which can be masked by ensemble inhomogeneous broadening. As shown by the circled points of interest in Figure 2, individual nanocrystals were selected for lifetime measurements.…”
mentioning
confidence: 99%
“…Results reported in literature almost all refer to the lowest energy 1S h -1S e absorption feature. So far the results do not take into account the homogeneous and ensemble broadening of first exciton peak and its dispersive behavior, while it has been clearly shown that the few or single isolated near-infrared lead chalcogenide nanocrystals have a spectral broadening of ~ 100 meV at room temperature [25,26]. The broad-band spectral dispersion has not been rigorously examined in carrier multiplication studies and its related efficiencies, though recent studies [10,12,27,28] have examined the bleach dynamics at discrete wavelengths within only the first exciton transition.…”
mentioning
confidence: 99%
“…There are many motivations for working in the near infrared, two of the most important being integrating new technologies into the photonics industry, which uses the infrared regions around 1300 nm and 1550 nm, and the development of NCs suitable for in vivo biological imaging around 800 nm where tissues are most transparent and there is minimal bioluminescence. 195 With regard to photonics, there are many emerging technologies being developed for these regions, including photonic band-gap materials 202,203 and high-Q microcavities. 204 Therefore developing new NC materials that emit in these regions could potentially be compatible with some exciting new technologies and ultimately have a commercial impact on the photonics industry.…”
Section: Conclusion/perspectivesmentioning
confidence: 99%